2017
DOI: 10.1186/s12885-017-3279-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential of extravasated platelet aggregation as a surrogate marker for overall survival in patients with advanced gastric cancer treated with preoperative docetaxel, cisplatin and S-1: a retrospective observational study

Abstract: BackgroundThe theory of extravasated platelet aggregation in cancer lesions was recently introduced. We investigated the association of platelet aggregation in gastric cancer stroma with clinicopathological features, chemotherapeutic response, pathological response, and survival.MethodsThe study comprised 78 patients with advanced gastric cancer who had undergone gastrectomy with or without combination of docetaxel, cisplatin and S-1 (DCS) as preoperative chemotherapy between 2005 and 2014. The patients were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…[24][25][26] However, the related mechanism of action remains largely unknown. 4 Although PLR, NLR, and other hematological markers including nutrition indicators have been established as effective prognostic factors for numerous types of cancers, [8][9][10][11] the relationship between these markers and chemotherapy resistance is also unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[24][25][26] However, the related mechanism of action remains largely unknown. 4 Although PLR, NLR, and other hematological markers including nutrition indicators have been established as effective prognostic factors for numerous types of cancers, [8][9][10][11] the relationship between these markers and chemotherapy resistance is also unclear.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that a primary lesion with platelet infiltration as CD42b positive cells revealed chemo-resistance. 4 We focused on the role of circulating platelets in this study. Circulating platelets attach and aggregate to the vascular wall via von Willebrand factor (vWF), which released from damaged endothelial cells by cisplatin-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various types of cancer cells, including PDAC cells, can activate platelets, which in turn, can support tumour cell growth and metastasis [ 10 , 42 , 43 , 44 ]. Recent clinical studies have indicated an association between platelets and poor chemotherapeutic responses in cancer patients [ 45 , 46 ]. However, the mechanisms by which platelets confer chemoresistance to cancer cells have remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…We previously found a correlation between extravasated platelet aggregation (EPA) and epithelial-mesenchymal transition (EMT) in breast cancer, and showed that patients with EPA were less responsive to neo-adjuvant chemotherapy ( 10 ). Furthermore, EPA in primary gastric cancer biopsy specimens was inversely correlated with pathological response to preoperative chemotherapy, and was identified as an independent prognostic factor ( 11 ).…”
Section: Introductionmentioning
confidence: 99%